2019
DOI: 10.1111/jwas.12656
|View full text |Cite
|
Sign up to set email alerts
|

Can artificial diets be a feasible alternative for the gonadal growth and maturation of the sea urchin Paracentrotus lividus (Lamarck, 1816)?

Abstract: Paracentrotus lividus (Lamarck 1816) has high-value reddishorange gonads that are regarded as a delicacy. In this study, three jellified diets have been tested for 90 days to assess the effect of different diets on P. lividus somatic and gonadal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 111 publications
1
4
0
Order By: Relevance
“…These results were also confirmed by comparison with the current literature. In fact, previous studies that administrated entirely vegetable diets to similar sea urchin size class (Vizzini et al, 2015;Santos et al, 2020b), obtained comparable GI values to those obtained in this study with D-0, but lower GI compared to D-20 and D-40. Furthermore, among the animal enriched diets tested in the present study, D-20 yielded the highest value of gonad index, as well as the lowest value of FCRg.…”
Section: Growth Performancessupporting
confidence: 81%
See 1 more Smart Citation
“…These results were also confirmed by comparison with the current literature. In fact, previous studies that administrated entirely vegetable diets to similar sea urchin size class (Vizzini et al, 2015;Santos et al, 2020b), obtained comparable GI values to those obtained in this study with D-0, but lower GI compared to D-20 and D-40. Furthermore, among the animal enriched diets tested in the present study, D-20 yielded the highest value of gonad index, as well as the lowest value of FCRg.…”
Section: Growth Performancessupporting
confidence: 81%
“…Vegetable and animal ingredients mixed in a formulated diet can, in fact, maximize sea urchin growth performance, reducing time for the production of high-quality marketable gonads (Vizzini et al, 2019). To date, several attempts have been made to obtain a good market product using a balanced mix of vegetable and animal sources, as alternative diets to traditional ones (Vizzini et al, 2015;Sartori and Gaion, 2016;Cirino et al, 2017;Fabbrocini et al, 2019;Raposo et al, 2019;Zupo et al, 2019;Ciriminna et al, 2020;Santos et al, 2020b;Ciriminna et al, 2021;Lourenco et al, 2021). However, as far as we know, only Fernandez and Boudouresque (2000) focused on a comparative investigation of the dietary requirements of the sea urchin during different life stages.…”
Section: Introductionmentioning
confidence: 99%
“…4 As demand continued to increase and the capture of wild sea urchins was no longer ecologically sustainable, interest in echinoculture emerged. [5][6][7][8][9] In fact, echinoculture, in addition to responding to the demand increase, has helped to relieve pressure from fishing in wild populations. 10 One of the main obstacles encountered in the production of sea urchins are related to feed: difficulty in finding the balance between cost and quality of feed, limited growth due to inadequate diets and poorly optimized and efficient feeding regimes.…”
Section: Introductionmentioning
confidence: 99%
“…7,[10][11][12][13] The negative aspects in the use of macroalgae in the feeding of sea urchins in aquaculture led to an increase in scientific research focused on their feeding, whose work found a common solution: the development of formulated diets. 2,9 In other hand, inert diets are easier to store, can be kept at room temperature and allow greater feed control because the nutritional characteristics of the feed are known and invariable throughout the year. 13 Several studies have also shown a greater somatic and gonadal growth in sea urchins when fed with inert diets.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is impractical and detrimental to the organism to have all its surface water removed, the more standardised the quantity of surface water on each urchin, the more precise the measurement will be. Certain papers mention specific units of time they allow urchins to drip‐dry before being weighed (Ellers & Johnson, 2009; Russell, 1998; Santos et al., 2020; Selden et al., 2009), but these papers do not all use the same units of time, and many other papers do not mention how long the urchins had been emersed before being weighed. Furthermore, the urchin mass measurements are likely influenced by the release of fluid when emersed.…”
Section: Introductionmentioning
confidence: 99%